Effects of the EQUIP quasi-experimental study testing a collaborative quality improvement approach for maternal and newborn health care in Tanzania and Uganda - Waiswa, Peter; Marx, Michael (Implementation science, 2017)
Quality improvement is a recommended strategy to improve implementation levels for evidence-based essential interventions, but experience of and evidence for its effects in low-resource settings are limited. We hypothesised that a systemic and collaborative quality improvement approach covering district, facility and community levels, supported by report cards generated through continuous household and health facility surveys, could improve the implementation levels and have a measurable population-level impact on coverage and quality of essential services.
Published online: 18 July 2017
Gesehen am 27.06.2018